ВРАХУВАННЯ В CЛАБКОЗВ’ЯЗАНІЙ КОЛО-ПОЛЬОВІЙ МОДЕЛІ АСИНХРОННОГО ДВИГУНА ВИТІСНЕННЯ НАВЕДЕНОГО СТРУМУ В КОЛІ РОТОРА - Головань, І.В.; Попович, О.М. (Інститут електродинаміки НАН України, Київ, 2025)
The paper presents an iterative-parametric method for solving the equations of a weakly coupled circuit-field model of an induction motor (IM), which takes into account the effect of current displacement in the rotor. The method involves iterative solving of the equations of the circuit and field mathematical models by refining the parameters of the IM’s equivalent circuit and iteratively adjusting the calculated electromagnetic torque to account for the current displacement effect, based on equivalent currents in the conductive parts of the rotor. This approach enhances the accuracy of modeling electromagnetic processes in IMs during start-up modes. The method was verified through the simulation of start-up modes for IMs with a squirrel-cage rotor and IMs with massive ferromagnetic elements in the magnetic core, allowing for the evaluation of the impact of current displacement on the additional torque, which is used to adjust the calculated electromagnetic torque of the circuit model. The study also justified the need for adapting the finite element mesh to ensure calculation accuracy when the current displacement effect significantly influences the results. References 26, table 1, figures 4.